Pulse oximeter for breathing signal analysis - Chin, Hui Chen (2018)
Pulse oximeter has serves its purpose not only in the hospitals and clinics, but it is increasingly being used at home for self-checking as well. This is because pulse oximeter uses non-invasive technique to measure; it is compact, cheap, and easy to use.